The Future of a Stalinist State: Albanian Science Fiction Literature during Communism - Sulstarova, Enis (Dějiny – teorie – kritika, 2022)
The article aims to show how the Albania of the future was imaged through the science fiction literature published in the country in the 1970s and 1980s, which was the “golden age” of this genre in Albania. Science fiction was considered to be a part of children’s and young adult literature that supplemented science education. Although the writers could envision what their country would look like in the next decades or centuries, they had to ground their imagination in sound scientific data, and they had to keep in mind the political realities of the present. Albanian science fiction literature reflected the fact that Stalinist Albania was one of the most isolated countries on the planet. Albania projected into the future was expected to be a highly developed country, whose spaceships, guided by pioneers, explored the universe, but at the same time it was vigilantly protecting its borders against capitalist and socialist revisionist states. Unlike what happened in other socialist countries in the post-Stalinist period, science fiction in Albania could not function as a subtle critique of reality and the Cold War. On the contrary, it served to limit the political horizon within which the children would grow up: while the imagined Albania of the future allegedly offered them limitless possibilities in technical and scientific achievements, they had to live in the same “frozen” socio-political system as in the present.